Critical judgement about the “responsabilidad de proteger” in international public law - Castaño, Sergio Raúl (Derecho Público Iberoamericano, 2017)
This paper aims to put into debate the controversial principle of the socalled “responsibility to protect” in international public law. After briefly pointing out the human and political value of the State independence and its recognition and validity in contemporary international law, the autor focuses on the idea of “responsibility to protect” in orden to underline its theoretical misunderstanding as well as the lack of legitimacy involved in the normalization of its practice.